Desain Pengembangan Kurikulum dan Implementasinya untuk Program Pendidikan Agama Islam - Muhammad Ghozil Aulia; Mohamad Agung Rokhimawan; Jauharotun Nafiisah (Journal of Education and Teaching (JET), 2022)
This study aims to find out about curriculum design and curriculum implementation in Islamic religious education. This research is a type of library research. This study uses a qualitative approach in understanding a phenomenon experienced by the subject or object of research, with descriptive methods in the form of words and language. This study contains a curriculum design design related to the preparation of curriculum elements in its planning used to facilitate the development of student potential in order to achieve educational goals. About curriculum design that exists in two dimensions, horizontal and vertical. Components of the curriculum in the organization in several categories. As well as the classification of curriculum design as a modification or combination of three main categories: subject-centered design, learner-centered design, and problem-centered design. In its application, the design of curriculum development, especially Islamic Religious Education in the scope of schools or madrasas, undergoes paradigm changes. The curriculum is designed and developed based on the needs, interests, and talents of students, taking into account the psychological aspects of students. Therefore, the design of the Islamic religious education curriculum must be designed and implemented as effectively as possible to facilitate students in learning.